Mechanical properties of thermally damaged mortar under coupled static-dynamic loading - Ying, Chengjuan; Chen, Haiming; Chen, Jie; Xiong, Liangxiao; Yao, Duoxi (Frontiers in Materials, 2024)
In buildings that experience fires, cement mortar is subjected to high-temperature environments and not only the weight of the structure above but also blast loads, leading to structural damage and loss of load-bearing capacity. To investigate the static and dynamic mechanical properties of thermally damaged mortar, a series of tests utilizing modified split Hopkinson pressure bar were conducted. These tests included quasi-static, conventional dynamic and coupled static-dynamic loading tests on mortar specimens that were subjected to seven temperature levels: 20℃, 100℃, 200℃, 300℃, 400℃, 500℃ and 600℃. The test results revealed that both the thermal damage and loading method had an impact on the mechanical properties and damage characteristics of the mortar specimens. The compressive strength, elastic modulus and absorbed energy ratio of mortar decreased as temperature increased. Notably, the quasi-static strength loss rate was 60% when the temperature reached 600℃. Under coupled static-dynamic loading, the specimens exhibited higher strength, elastic modulus, reflected energy ratio, and transmitted energy ratio. Conversely, they had lower average strain rates and absorbed energy ratios. Intriguingly, the dynamic growth factor had a relative increase of 0.7-2.0 compared with other loading methods. Furthermore, the higher temperature, the higher fragmentation of the specimens in the fragmentation pattern. Conventional dynamic loading resulted in the greatest degree of fragmentation. The findings provide a scientific basis for the design and evaluation of concrete shockproof and explosion-resistant structures.